Integrative analysis of Mazama temama (Artiodactyla: Cervidae) and designation of a neotype for the species - Sandoval, Eluzai Dinai Pinto [UNESP]; Rola, Luciana Diniz; Morales-Donoso, Jorge Alfonso [UNESP]; Gallina, Sonia; Reyna-Hurtado, Rafael; Duarte, Jose Maurício Barbanti [UNESP] (Oxford University Press (OUP), 2022)
Mazama temama is the smallest red deer in Central America. It was one of the first species described for the genus, and until the end of the last century many authors considered it as a subspecies of Mazama americana due to morphological similarities. Cytogenetic studies of animals in captivity have shown different karyotypes that led to its recognition as a unique species, and phylogenetic studies sustained the monophyly of the species, with some inconsistencies due to its wide geographical distribution. The objectives of the study were to characterize a topotype of Veracruz and three other specimens from a Campeche locality, to complement the description of M. temama and to propose a neotype for the species. We described this species morphologically (cranial measurements, skin color, and body biometry), and obtained karyorypes from wild animals with known origins for cytogenetic analyses (C band, G band, Ag-NOR, and Giemsa staining). We also performed phylogenetic analyses of Cytb, D-loop, COI, and ND5 mitochondrial genes. The morphometric results separated M. temama from M. americana but not from the other small Mazama species. The phylogenetic trees of mitochondrial genes Cytb, COI, and ND5 corroborated the monophyly of the species with 100% of posterior probability. The topotype's karyotype is significantly different from the one previously described for the species, and the other specimens from Campeche have karyotype variants whose chromosomal rearrangements are possibly the beginning of a reproductive isolation mechanism. We discussed the possibility to have more than one species of red brocket deer in Mexico and Central America.
Keywords: cervidos; deer; DNA mitocondrial; filogenia; Mexican red brocket; mitochondrial DNA; phylogeny; taxonomy; taxonomía; venado temazate